THE PROCEDURE FOR REGISTRATING THE LEGALITY OF MICRO,SMALL AND MEDIUM ENTERPRISES DAPUR OMA NANA AND JAWARA RASA CULINARY BUSINESS ON CV TRIBINA JASAINDO - Aida Agusti Resinta; Rahmi Ayunda (ConCEPt - Conference on Community Engagement Project, 2022)
Every business basically has to be legally licensed. Not only for large-scale businesses, but also for micro, small and medium enterprises. To establish Micro, Small and Medium Enterprises (MSMEs), entrepreneurs must have a license. The licensing that must be taken is adjusted to the types of MSMEs that you want to establish. The application for an industrial business license cannot be separated from the licensing system that applies in a government. The convoluted licensing system not only makes it difficult for applicants but also illustrates how badly the current system is. Licensing management using a bad system will have a negative impact both in administrative and technical terms. The purpose of this problem was raised into a writing, namely, to be able to provide an explanation and understanding of the importance of legal understanding for prospective entrepreneurs who want to make legality in Batam City because of the importance of an acknowledgment or legality from the Government in order to illustrate legal certainty. The benefits of having this activity carried out are, the author himself hopes that entrepreneurs in Batam City can understand the various ways in which the application process for making food MSME business permits online. This research is a legal research (juridical research) which has a method that is different from other research. The legal research method is a systematic way of conducting a research. The results of the output design are in the form of a Business License, NIB Letter (Business Registration Number) and Business Permit Attachments. Where in the business license it contains "the provisions of Article 31 of Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services.